2014
DOI: 10.1007/s00520-014-2406-x
|View full text |Cite
|
Sign up to set email alerts
|

GWAS of 972 autologous stem cell recipients with multiple myeloma identifies 11 genetic variants associated with chemotherapy-induced oral mucositis

Abstract: Purpose High-dose chemotherapy and autologous stem cell transplant (ASCT) to treat multiple myeloma (MM) and other cancers carries the risk of oral mucositis (OM) with sequelae including impaired nutritional and fluid intake, pain, and infectious complications. As a result of these problems, cancer treatment may have to be interrupted or delayed. In this study we looked beyond OM's known risk factors of renal function and melphalan dose with a genome-wide association study (GWAS) to evaluate whether genetic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 33 publications
0
10
1
Order By: Relevance
“…The two recent GWAS studies on patients that received HSCT identified SNPs near the locus of MMP and other genes related to inflammation, but none related to HLA-DR [17, 18]. Other recent studies found a major role for MMPs in mucositis pathology [57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The two recent GWAS studies on patients that received HSCT identified SNPs near the locus of MMP and other genes related to inflammation, but none related to HLA-DR [17, 18]. Other recent studies found a major role for MMPs in mucositis pathology [57].…”
Section: Discussionmentioning
confidence: 99%
“…Recent genome-wide association studies (GWAS) of patients that underwent HSCT have implied that UM development is associated with a genetic predisposition, primarily related to immune function [17, 18]. One study included 153 patients with miscellaneous malignancies that underwent HSCT, with the aim of building a predictive network for UM, based on 82 selected single nucleotide polymorphisms (SNPs) [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of the ten toxicities investigated by GWAS were represented by a single study (29,64,65,72), and only one of those four studies incorporated participants of non-European descent (Figure 2A) (65). Of the 28 total studies, 16 utilized cohorts of entirely European descent, compared to 6 that were entirely East Asian, and 6 studies with diverse cohorts (Figure 2B).…”
Section: Disparities In Gwas Population Representationmentioning
confidence: 99%
“…Such clinical heterogeneity confounds analyses unless rigorous care is taken during data collection and analysis. A number of studies evaluated in this review displayed heterogeneity of agents within a class, multiple primary agents, or multiple toxic drugs (55,63,68,72,73,76,77). Problems with accurately assessing phenotype and clinical heterogeneity are particularly troublesome when choosing and properly applying replication sets.…”
Section: Pharmacogenomic Challengesmentioning
confidence: 99%